FORMING OF IMAGE IN LANDSCAPE (Pedagogy of Higher and Secondary Education, 2022)
The theoretical and practical aspects of creation of image in landscape in the process of preparation of artists-teachers are examined in the article. Stages, maintenance and forms of work, are looked over, being based on methodical soil, as facilities of artistic education.